Improving reading skills across the content areas: Ready-to-use activities and assessments for grades 6 - 12 - Rozmiarek, Rebecca (Corwin Press, 2006)
A must-have, must-read resource for every teacher in all subject areas! In today's competitive environment of standards-based education, improving reading proficiency and increasing content knowledge have never been more important. Yet, developing exceptional reading skills in middle and high school students presents many obstacles. In this practical and user-friendly book, literacy specialist Rebecca Rozmiarek shares more than 100 classroom-tested reading activities that will benefit all students all secondary school students, including gifted and special education students, and students with English as an additional language. Incorporating years of success in helping struggling secondary students become expert readers, she provides both a jargon-free overview of critical research and activities that every teacher can use to improve reading comprehension and content retention. Student examples and sample modifications show teachers how reading activities can be used in content areas ranging from math and science to social studies and English, and more. Each chapter contains: o A skills overview o Detailed descriptions of relevant subskills o Skill-building activities o An assessment rubric o Examples of student work o Blank reproducibles of every activity Learn how to use double-entry journals, text coding, bookmarking, and questioning strategies to help students become more proficient readers. These activities foster independence, self-reflection, and motivation in all students.